Understanding Sorafenib-Induced Cardiovascular Toxicity: Mechanisms and Treatment Implications - Li J; Zhang L; Ge T; Liu J; Wang C; Yu Q (Dove Medical Press, 2024)
Jue Li,1,* Lusha Zhang,2,* Teng Ge,2 Jiping Liu,1 Chuan Wang,1 Qi Yu1,2 1Engineering Research Center of Brain Health Industry of Chinese Medicine, Key Laboratory of Pharmacodynamics and Material Basis of Chinese Medicine of Shaanxi Administration of Traditional Chinese Medicine, Pharmacology of Chinese medicine, Shaanxi University of Chinese Medicine, Xianyang, 712046, People's Republic of China; 2Shaanxi Key Laboratory of Ischemic Cardiovascular Diseases and Institute of Basic and Translational Medicine, Xi'an Medical University, Xi'an, 710021, People's Republic of China*These authors contributed equally to this workCorrespondence: Qi Yu; Chuan Wang, Email qiyu6028@hotmail.com; wangchuan@sntcm.edu.cnAbstract: Tyrosine kinase inhibitors (TKIs) have been recognized as crucial agents for treating various tumors, and one of their key targets is the intracellular site of the vascular endothelial growth factor receptor (VEGFR). While TKIs have demonstrated their effectiveness in solid tumor patients and increased life expectancy, they can also lead to adverse cardiovascular effects including hypertension, thromboembolism, cardiac ischemia, and left ventricular dysfunction. Among the TKIs, sorafenib was the first approved agent and it exerts anti-tumor effects on hepatocellular carcinoma (HCC) and renal cell carcinoma (RCC) by inhibiting angiogenesis and tumor cell proliferation through targeting VEGFR and RAF. Unfortunately, the adverse cardiovascular effects caused by sorafenib not only affect solid tumor patients but also limit its application in curing other diseases. This review explores the mechanisms underlying sorafenib-induced cardiovascular adverse effects, including endothelial dysfunction, mitochondrial dysfunction, endoplasmic reticulum stress, dysregulated autophagy, and ferroptosis. It also discusses potential treatment strategies, such as antioxidants and renin-angiotensin system inhibitors, and highlights the association between sorafenib-induced hypertension and treatment efficacy in cancer patients. Furthermore, emerging research suggests a link between sorafenib-induced glycolysis, drug resistance, and cardiovascular toxicity, necessitating further investigation. Overall, understanding these mechanisms is crucial for optimizing sorafenib therapy and minimizing cardiovascular risks in cancer patients.Keywords: sorafenib, vascular endothelial growth factor receptor, hypertension, cardiovascular toxicity, cancer